2016
DOI: 10.1038/ncomms13262
|View full text |Cite
|
Sign up to set email alerts
|

An enduring rapidly moving storm as a guide to Saturn’s Equatorial jet’s complex structure

Abstract: Saturn has an intense and broad eastward equatorial jet with a complex three-dimensional structure mixed with time variability. The equatorial region experiences strong seasonal insolation variations enhanced by ring shadowing, and three of the six known giant planetary-scale storms have developed in it. These factors make Saturn's equator a natural laboratory to test models of jets in giant planets. Here we report on a bright equatorial atmospheric feature imaged in 2015 that moved steadily at a high speed of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 63 publications
(170 reference statements)
6
24
0
Order By: Relevance
“…Previous measurements of the VIMS zonal winds in 2004–2008 (Choi et al, ), which have the roughly same time frame as the ISS wind profile (Figure ), suggest even stronger equatorial winds. Therefore, we think the equatorial zonal winds are stronger by at least 50 m/s at the 2,000 hPa pressure level than at the 300–500 hPa pressure level, which is consistent with the analysis in a previous study (Sanchez‐Lavega et al, ).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Previous measurements of the VIMS zonal winds in 2004–2008 (Choi et al, ), which have the roughly same time frame as the ISS wind profile (Figure ), suggest even stronger equatorial winds. Therefore, we think the equatorial zonal winds are stronger by at least 50 m/s at the 2,000 hPa pressure level than at the 300–500 hPa pressure level, which is consistent with the analysis in a previous study (Sanchez‐Lavega et al, ).…”
Section: Resultssupporting
confidence: 93%
“…Such a vertical shear of zonal winds in the middle and high latitudes is opposite to that in the equatorial region (5°S-5°N), in which the zonal winds are stronger at 2,000 hPa than at 300-500 hPa. It should be mentioned that it is also possible that the differences of zonal winds in the middle and high latitudes between the two pressure levels are due to the temporal variations, even though previous studies of the ISS winds (Garcia-Melendo, Perez-Hoyos, et al, 2011;Li et al, 2011;Sanchez-Lavega et al, 2016) and our examination of the temporal variations of the VIMS winds ( Figure 4) suggest that both of the ISS and VIMS zonal winds are likely stable over time in most latitudes.…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…A bright White Spot (WS) in the North Equatorial Zone (NEZ) at 6.7±1.6 • N appeared in 2014 and was visible in many amateur observations acquired in 2014 and 2015. Sánchez-Lavega et al (2016) reported on the properties of this feature based on Cassini ISS images, ground-based data and HST images acquired on 29-30 June 2015. The bright cloud moved at 450 ms −1 .…”
Section: Equatorial White Spot: 2014-2018 (Ls=58-106)mentioning
confidence: 99%